Prognotic Test for Mortality and Morbidity Using Procalcitonin and C-Reactive Protein Values in Elderly Patients Post Hip Joint Arthroplasty at Dr. Mohammad Hosein General Hosital Palembang - Nur Rachmat Lubis; Diah Mirlia; Irsan Saleh (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2020)
Background: Pelvic arthroplasty in the elderly is increasingly being performed, along with the increasing life expectancy in Indonesia. However, postoperative mortality must be taken into account. Methods: Prospective cohort study of mortality and morbidity up to 30 days in 38 patients who met the inclusion criteria. The observation of changes in the value of Procalcitonin and C-Reactive Protein was carried out preoperatively, after surgery on day 2 and after surgery on day 7. Results: There was no mortality. There was 18% redness output in the analyzed surgical wound. The cut off of Procalcitonin used Fisher's Exact test (RR = 3.088, p = 0.207), while the cut off of C-Reactive Protein used Fisher's Exact test (RR = 1.647, p = 0.678). Conclusion: There was no significant relationship between procalcitonin levels and C-reactive protein and postoperative redness.